Association of Blood Pressure with Body Mass Index and Waist Circumference and its Effects Among School Students (Aged 8-16 Years) of Rural West Bengal, India - Sengupta, Ratnabali; Ghorai, Narayan; Basu, Saikat Kumar (Journal of Bangladesh Academy of Sciences, 2016)
Body mass index (BMI) and waist circumference (WC) are considered as the most important anthropometric indicators to investigate the risk factors for cardiovascular diseases, hypertension and other obesity-related diseases. This study assessed the relationship between blood pressure (BP) with BMI and WC in students (aged 8 - 16 years) of rural West Bengal (WB) in Eastern India. About 551 rural secondary school going students were surveyed for BP, height, weight and WC. Among them 283 were boys and 268 were girls. BMI was derived using standard formula; Pearsons correlation coefficient was done to assess the degree of correlation among BP with BMI and WC. A lower range of obesity was found in rural areas in both boys and girls. WC was found to be more correlated with BP than BMI. Increase of BP was found with a higher BMI and WC. Prevalence of higher BP was found among school boys than girls in rural WB. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 169-178, 2016